1, 8‐Octanediamine Dihydroiodide‐Mediated Grain Boundary and Interface Passivation in Two‐Step‐Processed Perovskite Solar Cells. Issue 4 (19th January 2022) - Liu, Heng; Qi, Xingnan; Wang, Jiantao; Zhang, Weihai; Xia, Yu; Shi, Yueqing; Chen, Rui; Wang, Hsing-Lin
Abstract : Two‐step‐processed perovskite solar cells show superior reproducibility in terms of stepwise crystallization management. However, the device performance is limited due to the buried‐interface defects that are highly dependent on the diffusion process of organic salts into PbI2 . Herein, 1, 8‐octanediamine dihydroiodide (ODADI) is adopted to develop an alkylammonium predeposition strategy for the high‐quality perovskite film. It is found that the pre‐deposited ODADI layer not only facilitates the diffusion of organic salts via interaction with PbI2, but also passivates the buried‐interface defects, resulting in a perovskite film with low defect density, high crystallinity, and superior electronic properties. Consequently, the fabricated devices deliver a significant enhancement on power conversion efficiency (PCE) from 19.87 to 22.07%. In addition, a superior long‐term stability in glovebox atmosphere, maintaining 96% of the initial PCE after 1000 h, is demonstrated. Abstract : Highly efficient and stable perovskite solar cells via the two‐step method are fabricated by introducing a multifunctional 1, 8‐octanediamine dihydroiodide (ODADI) layer between electron transport layer and perovskite layer. It is found that the interfacial ODADI layer not only facilitates film crystallization but also reduces the buried‐interface defect density, delivering a significant enhancement on device efficiency from 19.87% to 22.07%.